Synthesis and characterization of La0.6Sr0.4Fe0.8Cu0.2O3-δ oxide as cathode for Intermediate Temperature Solid Oxide Fuel Cells - Vázquez, Santiago (2015)
Nanocrystalline La0.6Sr0.4Fe0.8Cu0.2O3-δ (LSFCu) material was synthetized by combustion method using EDTA as fuel/chelating agent and NH4NO3 as combustion promoter. Structural characterization using thermodiffraction data allowed to determine a reversible phase transition at 425 °C from a low temperature R-3c phase to a high temperature Pm-3m phase and to calculate the thermal expansion coefficient (TEC) of both phases. Important characteristics for cathode application as electronic conductivity and chemical compatibility with Ce0.9Gd0.1O2-δ (CGO) electrolyte were evaluated. LSFCu presented a p-type conductor behavior with maximum conductivity of 135 S cm-1 at 275 °C and showed a good stability with CGO electrolyte at high temperatures. This work confirmed that as prepared LSFCu has excellent microstructural characteristics and an electrical conductivity between 100 and 60 S cm-1 in the 500-700 °C range which is sufficiently high to work as intermediate temperature Solid Oxide Fuel Cells (IT-SOFCs) cathode. However a change in the thermal expansion coefficient consistent with a small oxygen loss process may affect the electrode-electrolyte interface during fabrication and operation of a SOFC.